Identifying asymptomatic healthcare workers with COVID-19 in a community hospital: an institution's experience - Neal Mehta; Krishna Vedala; Stephanie Swaim; Stephanie Welch; Amber Calendar; Krishna Kakkera; Khaled Khasawneh; Roy Kamoga (Greater Baltimore Medical Center, 2020)
The outbreak related to SARS-CoV-2 or COVID-19 has been classified as a pandemic. Many healthcare institutions enacted policies to limit the spread within their facility. As hospitals begin to return to normal particularly with elective procedures, a common concern is how an organization should react in the event that healthcare workers test positive for COVID-19. When our organization had a cluster of positive inpatient healthcare workers, we elected to test all direct patient care healthcare workers. Through this process we learned two valuable lessons that have redefined our practice: 1) the recognition that aggressive contact tracing provides greater yield than testing everyone and 2) organizations must implement effective social distancing both within each department and how departments interact with each other to limit the scope of contract tracing.